Realization of Teachersâ Questions to Uncover Studentsâ Cognitive Domain of English Subject Matter in Classroom Interaction - Kurniawati, Anita Rizky; Wuli Fitriati, Sri (English Education Journal, 2017)
When teachers conduct a lesson, the activity of posing questions always appears in it. The activity of posing questions includes the skills of asking cognitive level of questions in which a teacher must acquire. This study was undertaken in order to investigate the teachers questioning skill in asking cognitive level of questions during the teaching learning activity. Questioning which can reveal studentsâ mastery in the English subject matter was analyzed. In conducting the questioning, the purposes of the questions when they posed the questions and the ways the teachers keep their students active in responding their questions are also discussed. This discourse study was based on the analysis of the teacher talk in class. The analysis was based on the recorded data of the four English teachers when they conducted lessons in class. To collect the data, I used video recording, field notes, and interview. The recorded data was transcribed. From the transcription, the way the teachers ask question in asking cognititve level were analyzed based on the revision of Blooms Taxonomy (2001) and the way the teachers keep their students active in responding their questions were analyzed according to the questioning techniques proposed by Jacobsen (1999). Then, the data from interview were transcribed and the data from field notes were analyzed qualitatively. The findings show that the teachers posed all of the types of cognitive level of questions for various ways. Remembering questions were done to asses the extent to which studentsâ background knowledge were. In the understanding level, the questions train the studentsâ understanding to convey the information by using their own words. In the analyzing level, the questions require the students to use their analysis to solve the problem and use their logical reasoning to the question given. In the evaluating questions require the students to state the reason and think critically. In the creating question level require the students to create an original product based on the information given where they are driven to think creatively and critically. Related to the teachersâ purposes in posing the question, there are seven major points of the teachersâ purposes in posing question. Finally, the result is related to the way the teachers keep the students active in responding the questions. The teachers used all of the questioning techniques. They are redirection, probing, prompting, wait-time and rephrasing. It can be concluded that the teachers use all types of cognitive level of questions both for low level and high level questions. Although almost all of the questions delivered by the teachers is low level questions but the teachers has tried to give more high level questions.